1993
DOI: 10.1007/bf01296787
|View full text |Cite
|
Sign up to set email alerts
|

Study ofHelicobacter pylori colonization of patches of heterotopic gastric mucosa (HGM) at the upper esophagus

Abstract: Helicobacter pylori (HP), known to cause active chronic gastritis, has primarily been found in gastric-type mucosa. Even in the duodenum, the organism was detected in islands of metaplastic gastric mucosa. HP has also been found in gastric metaplasia of Barrett's esophagus in 15-50%. The aim of our study was to determine: (1) the frequency with which HP is found on histopathological sections of heterotopic gastric mucosa (HGM) patch(es) at the upper esophagus, as compared to that of the stomach proper, and (2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 12 publications
0
15
1
Order By: Relevance
“…Intestinal metaplasia is rarer in HGM, its incidence ranging from 0% to 12% [5,25,37,40,41]. In contrast to intestinal metaplasia of the gastric antrum, intestinal metaplasia in HGM does not seem to be correlated with H. pylori colonization of the inlet patch [6,25]. In our case the submucosa and muscularis mucosae located beneath intestinal metaplasia show the musculofibrous anomaly usually observed in Barrett's mucosa [35].…”
Section: Discussionmentioning
confidence: 66%
“…Intestinal metaplasia is rarer in HGM, its incidence ranging from 0% to 12% [5,25,37,40,41]. In contrast to intestinal metaplasia of the gastric antrum, intestinal metaplasia in HGM does not seem to be correlated with H. pylori colonization of the inlet patch [6,25]. In our case the submucosa and muscularis mucosae located beneath intestinal metaplasia show the musculofibrous anomaly usually observed in Barrett's mucosa [35].…”
Section: Discussionmentioning
confidence: 66%
“…This esophagitis has also been associated with stenosis, ulcers [11], and fistulae [12]. Helicobacter pylori infection, with associated gastritis, has been reported in islets of ectopic gastric mucosa [13]. In the present authors' series [10] goblet cells were observed in 1 of the 246 subjects but no Paneth cells were found.…”
Section: Esophageal Glands Propermentioning
confidence: 85%
“…18 The World Health Organization classifies this bacterium as a Type 1 carcinogen. 19 Although H. pylori infection is minimally invasive, metaplastic gastric tissue may also spread to other parts of the alimentary tract such as the duodenum, 20 the proximal esophagus, 21 the distal esophagus, 22 Meckel's diverticulum, 23 and the rectum. 24 In addition, it has been proposed that although H. pylori infection is circumscribed to the gastric mucosa, it could conceivably produce lesions remote to the primary site of infection, by altering levels of systemic inflammatory mediators.…”
Section: Association Between H Pylori Infection and Diseasementioning
confidence: 99%